Studies on Mechanical Attrition and Surface Analysis on Heat-Treated Nickel Alloy Developed through Additive Manufacturing - B. Anush Raj; J. T. Winowlin Jappes; M. Adam Khan; V. Dillibabu; N. Rajesh Jesudoss Hynes (Advances in Materials Science and Engineering)
In this paper, the nickel-based superalloy SU718 is developed through the Direct Metal Laser Sintering (DMLS), an additive manufacturing process. Further, the material has been focused to study the effect of heat treatment and abrasive particle erosion. Two different heat treatment (HT) cycles are planed with ageing and annealing to enrich the metallurgical quality of the DMLS processed SU718 alloy. The heat treatment is performed with two different combinations of temperatures for annealing/solutionizing followed by ageing to improve the metallurgical properties. The influence of heat treatment on additively manufactured IN718 is imparting variations in the hardness, microstructure, and erosion resistance. Vickers hardness for as built, HT 1, and HT 2 of DMLS alloy is 264.15, 385.55, and 352.43 Hv; which has been increased for 45% for HT 1 and 33% for HT 2 from the as built DMLS alloy. After solutionizing, the grains are refined within the track boundary and the majority of the grains are homogenized. The air jet erosion test arrangement is used to conduct the study at a velocity of 250 m/s and impact angle of 90° at room temperature. The hardness of the treated samples has taken vital role to resist the erosion. The rate of erosion is higher for bare DMLS alloy whereas HT 1 has low erosion rate when compared with HT 2 and bare DMLS alloy. The erosion morphology of the samples was carried out by SEM images, and erosion mechanism is discussed. The ploughing and microcutting were found in all the impact angles, whereas erodent impingement is found in the bare DMLS alloy in additional. The good erosion resistance is observed for HT 1 DMLS alloy in all the impact angles.